Factors Related to The Visit of Children Under Five in Obesi Village Integrated Healthcare Center - Ermy S. R. Mage; Rinawaty Sirait; Amelya Betsalonia Sir (Universitas Nusa Cendana, 2020)
The integrated healthcare center is a form of community-based health effort for monitoring the health and growth of toddlers as a strategy to reduce health problems, especially the toddler mortality rate. Mother’s behavior to visit integrated healthcare center is influenced by various factors. This study aims to analyze the factors related to the visit of children under five. This is an analytical study with a cross-sectional study design. This research was conducted in two integrated healthcare centers in Obesi Village in March 2020. The population of this study is 123 mothers. The sample size in this study was calculated using the Slovin formula obtained 95 mothers. Then sample calculation for each integrated healthcare center was carried out using the proportional simple random sampling formula. The data were collected using questionnaires and then analyzed using the chi-square test with a confidence level of 95% % . The results showed that maternal knowledge (p-value = 1,000), maternal attitude (p-value = 1,000), maternal occupation (p-value = 0,475), attitude of health workers (p-value = 1,000) are not related to the visits of children under five. But integrated healthcare center distance (p-value = 0,012) and husband’s support are related to the visits of children under five 2019 (p-value = 0,019). This study shows that the visits of children under five to integrated healthcare center is influenced by various factors, therefore it is recommended to the community and various related parties to support mothers of children under five in making visits to the integrated healthcare center.